Economic Burden Of Inappropriate Empiric Antibiotic Therapy: A Report From Southern Iran - Sadatsharifi, Arman (Risk Manag Healthc Policy, 2019)
INTRODUCTION: Widespread inappropriate antibiotic prescribing by healthcare professionals in the hospital setting is a great concern that may cause many undesirable consequences. Adherences to antibiotic guidelines have proven to be a simple and effective intervention to guide the choice of appropriate empiric antibiotic regimens and reduce the unnecessary variations in the practice among practitioners. The objective of this study was to evaluate the prescription patterns of empiric antibiotic therapy in relation to treatment guidelines and the economic burden of discordance with guidelines in a major referral Iranian university hospital. METHOD: Hospital records of hospitalized patients with empiric antibiotic prescription, from September 2016 to February 2017 were reviewed. The process consisted of comparing empiric antimicrobial administration with institutional guidelines for each patient by a clinical pharmacist and an infectious disease specialist to evaluate the appropriate utilization of antibiotics. Adherence to guideline, the cost of antibiotics usage for each patient and the excess cost consequent from discordance with guideline was calculated. RESULTS: The most inappropriate prescribed antibiotics were carbapenems and aminoglycosides. Overall guideline adherence was 27.8%. Frequency of antibiotic usage incompatibility with the guidelines on the basis of dosing interval, duration of therapy and drug indication were 31.46%, 29.44% and 19.36%, respectively. General surgery and internal medicine wards had the least and the most inappropriate antibiotic administration, respectively. Totally antibiotic usage cost was 578,959.39 USD (24,316,294,800 Iranian Rials, IRR) for 6 months, which the excess costs of inappropriate antibiotic prescribing, was 471,319.69 USD (19,795,427,225 IRR). The estimated annual excess cost is 942,639.38 USD (39,590,854,450 IRR). CONCLUSION: In this research, physicians’ adherence with guidelines for empiric antibiotic therapy was low which was led to 471,319.69 USD excess costs. These results urge institution policy makers to develop guidelines to ensure active dissemination and implementation of them to decrease inappropriate antibiotic usage.